2012
DOI: 10.1073/pnas.1208972109
|View full text |Cite
|
Sign up to set email alerts
|

Merck Ad5/HIV induces broad innate immune activation that predicts CD8 + T-cell responses but is attenuated by preexisting Ad5 immunity

Abstract: To better understand how innate immune responses to vaccination can lead to lasting protective immunity, we used a systems approach to define immune signatures in humans over 1 wk following MRKAd5/HIV vaccination that predicted subsequent HIV-specific T-cell responses. Within 24 h, striking increases in peripheral blood mononuclear cell gene expression associated with inflammation, IFN response, and myeloid cell trafficking occurred, and lymphocyte-specific transcripts decreased. These alterations were corrobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
127
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 69 publications
(65 reference statements)
9
127
1
1
Order By: Relevance
“…Based on the above observations, it is highly likely that some aspect of immune activation related to the use of Ad5 vectors in the vaccine led to the increased risk of infection. There is evidence that prevaccination anti-Ad5 titers correlated with altered early innate responses to the vaccine (49). Further, there is evidence that Ad5 immunization itself expands memory CD4 + T cells with a mucosal homing phenotype and that such CD4 + T cells are highly susceptible to HIV infection (16,50), which raises the possibility that vaccine-elicited CD4 + T cells provide an increased target population favoring transmission.…”
mentioning
confidence: 91%
“…Based on the above observations, it is highly likely that some aspect of immune activation related to the use of Ad5 vectors in the vaccine led to the increased risk of infection. There is evidence that prevaccination anti-Ad5 titers correlated with altered early innate responses to the vaccine (49). Further, there is evidence that Ad5 immunization itself expands memory CD4 + T cells with a mucosal homing phenotype and that such CD4 + T cells are highly susceptible to HIV infection (16,50), which raises the possibility that vaccine-elicited CD4 + T cells provide an increased target population favoring transmission.…”
mentioning
confidence: 91%
“…Recent advances have used the tools of systems biology to probe the immune response to vaccination in humans (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Novel systems biology techniques allow integration of hierarchical levels of information, leading to a deconvolution of the complexity of biological systems (33).…”
Section: Systems Vaccinology: Predicting Vaccine Efficacymentioning
confidence: 99%
“…S4), though this does not necessarily preclude its upregulation in the tissues. Notably, Zak et al observed a significant increase in IL-10 expression in the peripheral blood mononuclear cells of volunteers immunized with HAdV5 in a Phase 1B clinical trial, 7 suggesting that IL-10R blockade might have a more substantial effect in humans. The use of an immunogen containing an immunodominant murine epitope (peptide H, restricted by murine H-2D d and H-2L d ) may have obscured responses to other epitopes in HIVconsv that are relevant to control of HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…We did not assess the duration of antibody binding in vivo, but in a previous study of persistent LCMV infection, administration of aIL-10R antibody every 3 d significantly enhanced responses to a DNA vaccine, suggesting that the half-life may be 3 d or longer. 20 While we elected to transiently block IL-10 signaling due to the short-lived increase in IL-10 expression observed after adenoviral immunization in humans, 7 repeated administrations of aIL-10R could further increase immunogenicity. Once an IL-10-blocking strategy has been optimized, it will be important to test it in a suitable challenge model, such as a humanized mouse or macaque model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation